Exploring the structure and nucleic acid interactions of the Leishmania sp. telomerase reverse transcriptase N-terminal region - Paiva, Stephany Cacete de; Salvador, Guilherme Henrique Marchi [UNESP]; Barbosa, Patrick dos Santos; Oliveira, Hamine Cristina de [UNESP]; Fernandes, Carlos Alexandre Henrique; Ramos, Carlos H I; Fontes, Marcos Roberto de Mattos; Cano, Maria Isabel Nogueira (Elsevier, 2025)
Leishmaniasis is a neglected tropical disease caused by protozoans of the Leishmania genus, against which no effective treatment or control is available. Like other eukaryotes, parasite telomeres are maintained by telomerase, a ribonucleoprotein complex vital for genome stability. Its protein component, TERT (telomerase reverse transcriptase), presents four structural and functional domains, with the TEN (Telomerase N-terminal) and TRBD (Telomerase RNA-binding) located at its N-terminal. The enzyme also contains an RNA component that carries the template copied by the TERT during telomere elongation. Here, we show that the tertiary structure of Leishmania major TERT (LmTERT) is conserved compared to other eukaryotes. However, the LmTERT N-terminal (LmTERT-NT) portion shows structural changes not detected in the entire protein, mainly in the TEN domain. Besides the disordered elements, the TEN gains two long β-sheets but preserves the GQ motif and the residues in β-sheet 5 that interact with the TRAP motif. In both structures, a linker flanks the TEN and TRBD. The TRBD is partially conserved in both structures and contains the canonical QFP and T motifs, invariant residues, and the putative CP and two trypanosomatid-specific motifs (TSM) besides genus-specific amino acid substitutions. Despite the structural changes, the recombinant LmTERT-NT preserves a hydrophobic cavity that binds specifically and in the picomolar range to the telomeric G-rich DNA and the TER 5' end region. Thus, LmTERT-NT shares the canonical structural domains and motifs and is biochemically active. We discuss the importance of the TERT N-terminal region in the parasite's telomerase catalysis.